1999
DOI: 10.1136/jnnp.67.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen use and early onset Alzheimer's disease: a population-based study

Abstract: Estrogen use may be protective for Alzheimer's disease with late onset. However, the eVects on early onset Alzheimer's disease are unclear. This issue was studied in a population based setting. For each female patient, a female control was matched on age (within 5 years) and place of residence. Information on estrogen use and other risk factors were, for cases (n=109) and controls (n=119), collected from the next of kin by structured interview. The strength of the association between estrogen use and early ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 28 publications
0
68
0
Order By: Relevance
“…Reports that post-menopausal estrogen replacement therapy (ERT) 1 is clinically efficacious in delaying the onset of Alzheimer's disease (AD) (1) or improving cognition (2) in post-menopausal women have been corroborated by numerous studies (3)(4)(5). Reports questioning the validity of these retrospective studies (6) demonstrated that women with clinically defined AD have no improvement on specific cognitive tasks following short (2-15-month) trials of estrogen treatment.…”
mentioning
confidence: 99%
“…Reports that post-menopausal estrogen replacement therapy (ERT) 1 is clinically efficacious in delaying the onset of Alzheimer's disease (AD) (1) or improving cognition (2) in post-menopausal women have been corroborated by numerous studies (3)(4)(5). Reports questioning the validity of these retrospective studies (6) demonstrated that women with clinically defined AD have no improvement on specific cognitive tasks following short (2-15-month) trials of estrogen treatment.…”
mentioning
confidence: 99%
“…There was insufficient information in the studies to assess the effect of estrogen or progestogen with regard to formulation, dosage, duration, or time since last use. Results of three subsequent epidemiologic studies are conflicting but do not change the overall estimate of risk reduction in a meaningful way (31)(32)(33).…”
Section: Senile Dementia and Cognitive Impairmentmentioning
confidence: 92%
“…The epidemiologic trials that revealed the protective effects of hormone replacement therapy against Alzheimer's disease included those of Tang et al (1996), Paganini-Hill and Henderson (1996), Kawas et al (1997), Baldereschi et al (1998), Waring et al (1999, Slooter et al (1999), Zandi et al (2002), Henderson et al (2005), Shao et al (2012), Imtiaz et al (2017a) and Imtiaz et al (2017b). In all the trials, the relative risks of developing Alzheimer's disease in the study participants subjected to hormone replacement therapy were less than one (<1) which indicated protective effects (these findings are presented in Table 1).…”
Section: Protective Association Between Hrt and Alzheimer's Diseasementioning
confidence: 99%
“…Other studies such as the Baltimore Longitudinal study (Kawas et al, 1997), Rochester population-based (Waring et al, 1999), Rotterdam population-based (Slooter et al, 1999), and the Multi-Institutional Research on Alzheimer's disease (Henderson et al, 2005) all revealed the protective effects of estrogen in AD after adjusting for other covariates such as age and educational status. This 'estrogen effect' could be attributed to Cholinergic mechanisms and other neuroprotective effects (Henderson, 1997).…”
Section: Protective Association Between Hrt and Alzheimer's Diseasementioning
confidence: 99%